Analysis of selected nutritional and environmental factors leading to the development of neural tube defects - Adrianna Pacołta; Marcelina Nalepka; Mikołaj Pograniczny; Adrianna Mielżyńska; Jakub Pochopień; Aleksandra Nowicka; Marlena Jankowska; Karolina Baran; Natalia Jańczyk; Michał Presak (Quality in Sport)
Neural tube defects represent the most common type of congenital central nervous system malformations. This study focuses on analyzing selected nutritional and environmental factors influencing neural tube development and their roles in the pathogenesis of these defects. A review of the literature, along with an analysis of clinical and experimental research results, has enabled the identification of molecular mechanisms such as the regulation of DNA methylation processes, homocysteine metabolism, and the teratogenic effects of environmental factors. A clinically significant association has been observed between the prenatal administration of vitamin B12 and folic acid and the risk of neural tube defects. The study also examines prenatal exposure to valproic acid, which carries the risk of neural tube defects, and discusses the role of choline, which appears to be important in supporting neurogenic processes. The work emphasizes the necessity of an interdisciplinary approach to the prevention of neural tube defects through the optimization of maternal nutrition and the elimination of harmful environmental factors.